Factor of Zoom cloud meetings: Technology adoption in the pandemic of COVID-19 - Zulherman Zulherman; Zalik Nuryana; Astadi Pangarso; Farah Mohamad Zain (Institute of Advanced Engineering and Science, 2021)
The purpose of this study was to prove the factors that influence the use of online learning platforms used in the COVID-19 pandemic. This study used quantitative methods to analyze the validity and reliability of items and to test hypotheses. This study employed the theory of UTAUT2 models with several other variables. The total participants in this questionnaire were 175 people: lecturers, teachers, and students at the university and were randomly drawn. Consists of ten independent variables and one dependent variable. The findings of this study on ten hypotheses were only two accepted and eight rejected but. the authenticity of this study was never investigated about the purpose of using the Zoom platform during the COVID-19 pandemic in the context of education in Indonesia.